Chromosomal aberrations induced by 5-azacytidine combined with VP-16 (etoposide) in CHO-K1 and XRS-5 cell lines - Guimaraes, APA; Dias, F. L.; Cardoso, R. S.; Kronka, S. N.; Sakamoto-Hojo, E. T. (Wiley-Blackwell, 2003)
A cytogenetic study was carried out with 5-azacytidine (5-azaC) and etoposide (VP-16) in CHO-K1 and XRS-5 (mutant cells deficient for double-strand break rejoining) cell lines to verify the interaction effects of the drugs in terms of induction of chromosomal aberrations. 5-azaC is incorporated into DNA causing DNA hypomethylation, and VP-16 (inhibitor of topoisomerase 11 enzyme) is a potent clastogenic agent. Cells in exponential growth were treated with 5-azaC for I h, following incubation for 7 h, and posttreatment with VP16 for the last 3 h. In K1 cells, the combined treatments induced a significant reduction in the aberrations induced in the X and A (autosome) chromosomes, which are the main target for 5-azaC. However, in XRS-5 cells, the drug combination caused a significant increase in the aberrations induced in those chromosomes, but with a concomitant reduction in the randomly induced-aberrations. In addition, each cell line presented characteristic cell cycle kinetics; while the combined treatment induced an S-arrest in K1 cells, alterations in cell cycle progression were not found for XRS-5, although each drug alone caused a G2-arrest. The different cell responses presented by the cell lines may be explained on the basis of the evidence that alterations in chromatin structure caused by 5-aza-C probably occur to a different extent in K1 and XRS-5 cells, since the mutant cells present a typical hyper-condensed chromosome structure (especially the X- and A chromosomes), but, alternatively, 5-aza-C could induce reactivation of DNA repair genes in XRS-5 cells. Teratogenesis Carcinog. Mutagen. Suppl. 1:171-186, 2003. (C) 2003 Wiley-Liss, Inc.
Keywords: 5-azacytidine; etoposide; chromosomal aberrations; DNA methylation